Logic for fun : solving puzzles with SAT solvers - Foo, Zhong Xian (2016)
Over the years, SAT solvers have become more and more powerful; able to solve Boolean formulas with huge amounts of literals and clauses, and have seen more applications in recent technology. Decision puzzles, puzzles where one move affects subsequent moves, usually take a long time to solve using typical depth first search algorithms, while SAT solvers can solve it relatively quickly.